High performance lead-free piezoelectric 0.96(K0.48Na0.52)NbO3-0.03[Bi0.5(Na0.7K0.2Li0.1)0.5]ZrO3-0.01(Bi0.5Na0.5)TiO3 single crystals grown by solid state crystal growth and their phase relations. Issue 15 (December 2017) - Uwiragiye, Eugenie; Farooq, Muhammad Umer; Moon, Su-Hyun; Pham, Thuy Linh; Nguyen, Dang Thanh; Lee, Jong-Sook; Fisher, John G.
Abstract: 0.96(K0.48 Na0.52 )NbO3 -0.03[Bi0.5 (Na0.7 K0.2 Li0.1 )0.5 ]ZrO3 -0.01(Bi0.5 Na0.5 )TiO3 single crystals were grown for the first time by the solid state crystal growth method, using [001] or [110]-oriented KTaO3 seed crystals. The grown single crystal shows a dielectric constant of 2720 and polarization-electric field loops of a lossy normal ferroelectric, with Pr = 45 μC/cm 2 and Ec = 14.9 kV/cm, while the polycrystalline samples with a dielectric constant of 828 were too leaky for P-E measurement due to humidity effects. The single crystal has orthorhombic symmetry at room temperature. Dielectric permittivity peaks at 26 °C and 311 °C, respectively, are attributed to rhombohedral-orthorhombic and tetragonal–cubic phase transitions. Additionally, Raman scattering shows the presence of an orthorhombic-tetragonal phase transition at ∼150 °C, which is not indicated in the permittivity curves but by the loss tangent anomalies. A transition around 700 °C in the high temperature dc conductivity is suggested to be a ferroelastic-paraelastic transition.